Innovative design of a vertical and transverse elevator in double shafts, based on TRIZ theory - Chen, Jiwen (Strojniški vestnik, 2019)
With the rapid growth of urban populations, the scale of modern buildings is expanding, and the span of buildings is increasing. Traditional elevators can only solve the problem of vertical transportation. Passengers still need to spend time walking to their destination after leaving the elevator. Based on the theory of inventive problem solving (TRIZ), this paper uses functional models, causal analysis, conflict analysis, the Su-Field model, and other tools to innovate on the basis of traditional elevators. A vertical and transverse elevator design proposal for double shafts structures and corresponding control strategies is proposed. Based on C, simulations of the effect of the vertical and transverse elevator on the passenger mobility efficiency are conducted in an 8-story building at different transverse distances and densities. The simulation results show that the vertical and transverse elevator can effectively improve the mobility efficiency of passengers in the horizontal direction in the studied environment, and the mobility efficiency of all passengers also significantly improves. As the transverse distance increases, the mobility efficiency of all passengers using the proposed elevator also increases.
Keywords: elevator passenger flow model; model Su-Field; Poisson distribution; Su-Field model; transverse elevators; transverzalna dvigala; TRIZ